2017
DOI: 10.1111/jdv.14676
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of ‘not relevant’ responses on the DLQI in psoriasis: potential biases in treatment decisions

Abstract: The high rate of psoriasis patients with NRRs, especially among women, less educated and elderly patients, indicates a content validity problem of the measure. A reconsideration of the use of the DLQI for medical and financial decision-making in psoriasis patients is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
4
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(84 citation statements)
references
References 67 publications
3
68
4
3
Order By: Relevance
“…Very few authors reported on the total number of NRRs in patients with psoriasis, and only one study indicated the rate of patients with more than one NRR . According to these data, on average 5–39% of people across populations of patients with psoriasis marked at least one NRR . As not all patients are affected by NRRs, it may be tempting to interpret scores based on DLQI‐R using the same MCID and score bandings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Very few authors reported on the total number of NRRs in patients with psoriasis, and only one study indicated the rate of patients with more than one NRR . According to these data, on average 5–39% of people across populations of patients with psoriasis marked at least one NRR . As not all patients are affected by NRRs, it may be tempting to interpret scores based on DLQI‐R using the same MCID and score bandings.…”
Section: Discussionmentioning
confidence: 99%
“…8 According to these data, on average 5-39% of people across populations of patients with psoriasis marked at least one NRR. 9,21,31,32,[38][39][40] As not all patients are affected by NRRs, it may be tempting to interpret scores based on DLQI-R using the same MCID and score bandings. Nevertheless, a formal study with anchoring questions is warranted to test the potential need to modify the DLQI banding when using DLQI-R instead of DLQI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Autoimmune blistering diseases including pemphigus are reported to cause one of the largest HRQoL impairment among chronic skin diseases . HRQoL outcomes are increasingly being recognized as an important tool to aid treatment decisions in dermatology . A method to quantify the HRQoL loss from disease and the HRQoL benefits of treatments is the assessment of health utility values.…”
Section: Introductionmentioning
confidence: 99%